2020
DOI: 10.1590/1678-4685-gmb-2019-0104
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and interplay between base and nucleotide excision repair pathways: From DNA lesions to proteins

Abstract: Base and nucleotide excision repair (BER and NER) pathways are normally associated with removal of specific types of DNA damage: small base modifications (such as those induced by DNA oxidation) and bulky DNA lesions (such as those induced by ultraviolet or chemical carcinogens), respectively. However, growing evidence indicates that this scenario is much more complex and these pathways exchange proteins and cooperate with each other in the repair of specific lesions. In this review, we highlight studies discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 120 publications
0
40
0
Order By: Relevance
“…NER-dependent DNA repair is carried out by six factors: replication protein A (RPA), Xeroderma Pigmentosum Complementation Group A, (XPA), Xeroderma Pigmentosum Complementation Group C (XPC) complexed with RAD23 Homolog B (HR23), Transcription factor II Human (TFIIH), Xeroderma Pigmentosum Complementation Group G (XPG), and Xeroderma Pigmentosum Complementation Group F (XPF). For a detailed view of this process the reader is referred to in-depth reviews [164][165][166]. In pioneering studies led by Aziz Sancar's group, NER mediated activity was shown to be rhythmic in brain [167] and liver, but not in testis [168] and skin [169].…”
Section: Cellular Processesmentioning
confidence: 99%
“…NER-dependent DNA repair is carried out by six factors: replication protein A (RPA), Xeroderma Pigmentosum Complementation Group A, (XPA), Xeroderma Pigmentosum Complementation Group C (XPC) complexed with RAD23 Homolog B (HR23), Transcription factor II Human (TFIIH), Xeroderma Pigmentosum Complementation Group G (XPG), and Xeroderma Pigmentosum Complementation Group F (XPF). For a detailed view of this process the reader is referred to in-depth reviews [164][165][166]. In pioneering studies led by Aziz Sancar's group, NER mediated activity was shown to be rhythmic in brain [167] and liver, but not in testis [168] and skin [169].…”
Section: Cellular Processesmentioning
confidence: 99%
“…Nucleotide excision repair can be further subcategorized into two pathways: global genome NER (GG-NER) and transcription-coupled NER (TC-NER), which are distinguished based on how the lesions are initially recognized [ 52 ]. The crosstalk between NER protein and BER proteins in the removal of oxidative damage has been reviewed [ 53 , 54 , 55 ]. The role for a GG-NER recognition protein, XPC, in stimulation of SMUG1 activity was demonstrated by the Sugasawa group [ 56 ].…”
Section: Moonlighting Functions Of Smug1 Outside Bermentioning
confidence: 99%
“…Finally, DNA-protein crosslinks are mainly repaired by HR. However, repair of DNA adducts can itself cause mutations, because intermediary steps generate abasic sites or strand breaks, which, if the repair process is not completed in a timely fashion, can lead to mutations [121][122][123]. Since DNA adducts cause genome instability, they result in loss of normal growth-control mechanisms and hence promote carcinogenesis.…”
Section: Pathways Producing the Metabolite Predicted Impacts On Genommentioning
confidence: 99%